Virtual environment as aids in persuading user in learning process - Yusoff, Mohd Fitri; Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana (2010)
With the advent of computing technologies, a plethora of computer applications were developed to solve simple to complex human and organization problems. Computer applications cover variety of fields and have been known to be powerful tools in changing person‘s attitudes, behaviours, feelings and actions. This paper investigates the use of virtual environment technology as aids in persuading users in learning process. It explains the concept of persuasive and virtual environment technologies and the integration of both technologies in persuading learners to learn. It elaborates on the design of persuasion and explains the benefits of integrating persuasive and virtual environment technologies in the learning process. Finally, it gives an overview of a proposed approach in utilizing virtual environment as aids in persuasive design for learning.